Multilayer cattle farming: a new dimension towards waste management and environmental sustainability in Bangladesh - Sarkar, SK; Uddin, MK (Bangladesh Journal of Livestock Research, 2020)
An on-station study was conducted at demonstration farm of Rural Development Academy (RDA) Bogra, Bangladesh with objectives to determine the impact of multilayer (two storied) cattle farming on food security for achieving economical and environmental sustainability. A two storied shed for cattle rearing were built with 10:1 slope for easy drainage and disposal of urine, faeces, wash water, feed refusals to a biogas plant directly for anaerobic digestion. About 70-80% waste materials was automatically and the rest amount was transferred manually. Per annum total waste 787.67 tons was used and produced 28356 m3 biogas and 157.53 tons of organic manure. Gross return of Tk. 24,61,272 and gross profit of Tk. 1145672 was made on a capital investment for Tk. 13,15,600. The benefit cost ratio (BCR) found 1:1.87. Compared to conventional, multilayer farming significantly higher amount of fresh manure was collected. In conventional farming, on an average 39.4% of manure is lost due to rain and flood caused contamination of water and threat to public health. The analysis of per day income from a cow was significantly (p<0.01) higher in multilayer farming system compare to conventional system. The average income from manure was Tk. 24.14 and Tk. 4.62/cow, respectively. Thus, it may be concluded that multilayer cattle farming may be more profitable and effective for waste processing, reduction of pollution and sustainable development of environment. Bangladesh J. of Livestock Res. 20(1-2): 101-111, Jan-Dec 2013